(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s
(3ChdgG (B:s
(3Qhi Yf GHf YHGS QVj Gddg Yfg Cfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde HjfeG CfG eGFe Hjf GdUaG hGdeQhI aj djdI PGJ QYO hHQb hShGOs
(3BNQgG (B:s
(3jLGgO aj SHjd Gddg MJi CYdG cdeI GdOjf hQaY CYdG GdeDefjf hYHO Gddg MJi CJGg Gdjbjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs